Spectrophotometric Determination of Sulfamethoxazole and Sulfadiazine in Pure and Pharmaceuticals Preparation - A. Dhahir, Saadiyah; H. Mhemeed, Amal (Asian Journal of Chemistry, 2012)
A rapid and sensitive spectrophotometric method is proposed for the determination of sulfamethoxazole and sulfadiazine. This method is based on the diazotization of sulfonamide with sodium nitrite and a coupling reaction of the diazo-compound with thymol. The optimum reaction conditions and other analytical parameters were evaluated. The linear ranges for the determination of sulfamethoxazole and sulfadiazine are 1-10 μg mL-1 and 1-7 μg mL-1 and their detection limits are 0.008 μg mL-1 and 0.007 μg mL-1 respectively. There was no interference from commonly utilized tablet excipients. The method has been used to determine sulfamethoxazole and sulfadiazine in pharmaceuticals preparation without separation.